А Comparative Analysis of Russian and Chinese Energy Supply Legislation - CHEKULAEV, Sergey; KARPOVA, Julia; DRACHEV, Artem (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).11, 2019)
The interaction and cooperation of Russia and China in this area requires the identification and analysis of the advantages and disadvantages of legal regulation of relations in the field of energy supply. The legal construction of an energy supply contract is regulated by the Civil Code of Russia and the Law of China ‘On Contracts’ for the contractual regulation of relations in the supply of electrical and (or) thermal energy to consumers through an attached network. The purpose of the study is to identify trends in the development of contractual relations in energy supply by using the Russian doctrine and the regulatory documents of Russia and China as materials. The subject of study is the doctrine (theoretical studies) of Russian legal specialists in the field of energy supply contracts; current legislation and regulations of Russia and China regulating relations in the studied area. The results of this study can be used to improve Russian legal acts regulating the relations in the field of energy supply. The study contains practical recommendations for the participants in civil legal relations, courts and other law enforcement agencies (for example, energy commissions, anti-monopoly authorities) in dealing with cases related to energy supply.